Permanent pacemaker implantation via the femoral vein: An effective and safe alternative - Freitas Rafael, Julianny; Moura de Souza Rangel, Lucas; de Castro Lacerda, Gustavo; Minati Barbosa, Rodrigo (JOURNAL OF CARDIAC ARRHYTHMIAS, 2018)
A 26-year-old male with systemic lupus erythematosus with hemodialysis nephritis had an infectious endocarditis of the aortic valve with abscess in the fibrous septum with flow into the right cavity. Being indicated aortic valve replacement and closure of the septal orifice with pericardial patch. The patient evolved after the procedure with total atrioventricular block (BAVT), and a definitive pacemaker (PM) was implanted by right subclavian vein (RSV). After six months, he presented an infected hematoma in the device, being explanted. As the patient was device dependent, temporary femoral vein (FV) was placed in the right ventricle (RV), until the resolution of the infectious condition and the release to implant of a new endocardial system. However, due to the presence of arteriovenous fistula (AVF) in the left upper limb (LUL) and right subclavian vein thrombosis diagnosed by venography, we opted for epicardial PM implantation. Twenty-three days after this implant evolved with failed capture by increasing stimulation threshold. New provisional PM was placed by FV. An attempt was made to implant PM by right internal jugular vein, without success, for non-progression of the guide (thrombosis). We chose to implant the definitive PM by right FV, with an electrode of 85cm and implant of a generating unit in the right iliac fossa. Ventricular threshold and impedance remained stable throughout the hospitalization. He was discharged, with evaluation after 6 months without intercurrences, with good threshold and impedance. The femoral route is an unusual but safe and effective alternative for definitive MP implantation in patients where high central and epicardial access is not possible.